Fostering Inclusive Entrepreneurship in South African Townships: A Contextual Analysis - (:unkn) unknown (My University, 2021)
Research has revealed a persistently low level of entrepreneurial activity among the Black South Africans, the majority of whom live in the townships. And the government has a major concern regarding the level of unemployment and poverty faced by this population group. It has therefore put into place a number of programs to foster entrepreneurship in order to develop the economy and employment. Despite these efforts, the level of entrepreneurship among Black South Africans, who constitute the majority of the population, has consistently remained low. This qualitative study, applying critical realism ontology, examines how a historical institution like apartheid through its racial discrimination policies may still affect current entrepreneurial behaviour. The outcome demonstrates the presence of active apartheid social mechanisms, and the effects of their underlying institutional logics on entrepreneurial behaviour. This may be useful in designing more efficient programmes to foster entrepreneurship within the township spatial context. The study contributes to the areas of entrepreneurship context, entrepreneurial motives, and entrepreneurial behaviour in relation to the understudied micro level effects of legacies of previously dominant institutional logics.
Keywords: African Research